Generation of Tfap2c‐T2A‐tdTomato knock‐in reporter rats via adeno‐associated virus‐mediated efficient gene targeting. Issue 3 (15th February 2022) - Oikawa, Mami; Nagae, Mayuko; Mizuno, Naoaki; Iwatsuki, Kenyu; Yoshida, Fumika; Inoue, Naoko; Uenoyama, Yoshihisa; Tsukamura, Hiroko; Nakauchi, Hiromitsu; Hirabayashi, Masumi; Kobayashi, Toshihiro
Abstract: Gene editing in mammalian zygotes enables us to generate genetically modified animals rapidly and efficiently. In this study, we compare multiple gene targeting strategies in rat zygotes by generating a novel knock‐in reporter rat line to visualize the expression pattern of transcription factor AP‐2 gamma ( Tfap2c ). The targeting vector is designed to replace the stop codon of Tfap2c with T2A‐tdTomato sequence. We show that the combination of electroporation‐mediated transduction of CRISPR/Cas9 components with adeno‐associated virus‐mediated transduction of the targeting vector is the most efficient in generating the targeted rat line. The Tfap2c‐T2A‐tdTomato fluorescence reflects the endogenous expression pattern of Tfap2c in preimplantation embryo, germline, placenta, and forebrain during rat embryo development. The reporter line generated here will be a reliable resource for identifying and purifying Tfap2c expressing cells in rats, and the gene targeting strategy we used can be widely applied for generating desired animals.